Technology and problem-based learning - Uden, Lorna 1946- (IGI Global (701 E. Chocolate Ave., Hershey, PA, 17033, USA), 2006)
"This book is aimed at educators who may be considering introducing problem-based learning and need to know what it involves, its benefits and the practical details of how to implement it"--Provided by publisher
Includes bibliographical references and index. - Title from PDF t.p. (viewed on July 27, 2010)
Keywords: Problem-based learning; Educational technology